Enhanced Optical Third-Harmonic Generation in Phase-Engineered MoTe2Thin Films - Ha, Seongju; Kim, Hyeonkyeong; Nam, Hyunjun; Choi, Jungseok; Chae, Kwanbyung; Lee, Jae Ung; Park, Ji Yong; Yoo, Youngdong; Yeom, Dong Il (ACS Photonics, 2022)
Molybdenum ditelluride (MoTe2) is a relatively unexplored layered transition metal dichalcogenide in nonlinear optics. Several recent studies have shown that MoTe2 has strong second-order optical nonlinearities originating from tellurium atoms. However, the third-order optical nonlinearities of MoTe2 have not been explored yet, except for the nonparametric saturable absorption process. Here we report the enhanced optical third-harmonic generation in phase-engineered MoTe2 thin films. MoTe2 films, including 2H and 1T′ phases simultaneously, are synthesized by the flux-controlled phase-engineering method, and their nonlinear response is characterized. We observe that the 2H-MoTe2 film exhibits up to a 15-fold stronger nonlinear signal than that of the 1T′-phase film. The estimated third-order effective nonlinear susceptibility of 2H-MoTe2 is 9.3 × 10-19 m2 V-2 maximum, which is larger than highly nonlinear layered materials such as molybdenum disulfide. Our MoTe2 film synthesized with the desired phase over a large area will be a potential building block for ultrathin nonlinear photonics.
Keywords: Dichalcogenides; In-phase; Optical third-harmonic generation; Structural phasis; Synthesised; Thin-films; Third order optical susceptibility; Third-harmonic generation; Transition metal dichalcogenides; Transition metal dichalcogenides (TMD); molybdenum ditelluride; nonlinear optics; structural phase; third-harmonic generation; third-order optical susceptibility; transition metal dichalcogenides